2020
DOI: 10.1111/bcp.14626
|View full text |Cite
|
Sign up to set email alerts
|

Impact of CYP2D6 on serum concentrations of flupentixol, haloperidol, perphenazine and zuclopenthixol

Abstract: To investigate the impact of cytochrome P450 2D6 (CYP2D6) on dose-adjusted serum concentrations of flupentixol, haloperidol, perphenazine and zuclopenthixol in a therapeutic drug monitoring (TDM) cohort of psychiatric patients. We also studied the functional impact of CYP2D6*41 on dose-adjusted serum concentrations in the perphenazine-treated patients. Methods: Serum concentrations of flupentixol, haloperidol, perphenazine and zuclopenthixol from CYP-genotyped patients were extracted retrospectively from a rou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 18 publications
0
11
0
Order By: Relevance
“… 13 Recently, authors found evidence that the functional impact of CYP2D6*41 on dose‐adjusted serum levels of patients treated with perphenazine was similar to that of null function alleles. 14 …”
Section: Discussionmentioning
confidence: 99%
“… 13 Recently, authors found evidence that the functional impact of CYP2D6*41 on dose‐adjusted serum levels of patients treated with perphenazine was similar to that of null function alleles. 14 …”
Section: Discussionmentioning
confidence: 99%
“…Particularly, CYP2D6 plays a key role in the metabolism of psychiatric drugs, including many antidepressants and antipsychotics, but it is also of importance for antiarrhythmics, antiemetics, β-adrenoceptor antagonists (β-blockers), opioids, and anticancer drugs [ 1 ]. The CYP2D6 gene is highly polymorphic leading to extensive interindividual variability of enzyme activity and systemic exposure of CYP2D6 drugs [ 2 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, the difference may also be due to the naturalistic setting of the data sets in this study, compared with a controlled population. Both perphenazine and zuclopenthixol have been found to be strongly influenced by the metabolic status of the CYP2D6 enzyme [ 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 ]. For these drugs, patients prescribed a standard dosage and who are either poor metabolisers or subject to drug interactions are expected to harbour a higher serum concentration.…”
Section: Discussionmentioning
confidence: 99%